Printing parameters of layer thickness in 3D printing digital light processing on absolute marginal discrepancy and marginal gap in hybrid ceramic-resin crown - Donny Tannu; Syafrinani; Ariyani (Indonesia Prosthodontic Association, 2025)
ABSTRACT Marginal adaptation in the form of absolute marginal discrepancy and marginal gap is one of the parameters for long-term clinical success in single crown restorations. The use of 3D printing digital light processing (DLP) additive manufacturing technology can produce accurate and efficient restorations. However, one of the printing parameter, layer thickness, can affect the accuracy of marginal adaptation. This review aims to evaluate the effect of layer thickness variation on absolute marginal discrepancy and marginal gap in definitive hybrid ceramic-resin crown manufactured using 3D DLP printing technology. Results show that a layer thickness parameter of 50 µm is preferred for good fitting accuracy and small cumulative deviation. Smaller layer thickness will increase the number of layers, and manufacturing time but on the other hand will reduce accuracy. Optimalization of the layer thickness is required to obtain the best marginal adaptation of a single crown. Keywords: Absolute marginal discrepancy; Marginal gap; layer thickness; 3D printing DLP; Hybrid ceramic-resin